Unsur Tenaga Gerak dan Penerapannya pada Tari Seudati: Proses Kreatif di Sanggar Aneuk Metuah, Aceh Besar - Sabri Gusmail; Prastika Dewi Nugra (Dance and Theatre Review, 2021)
The Element of Motion and Its Application in Seudati Dance: The Creative Process at Aneuk Metuah Studio, Aceh Besar. This article is the research result which was conducted in Aceh Besar, which led to training activities to solve problems that occurred in the Aneuk Metuah Studio. The problem with the studio is about the dancers’ body resistance when dancing the Seudati dance, namely that the dancers get tired quickly, which impacts the quality of the dance movement. The program is oriented towards increasing creativity in managing the energy element when dancing the Seudati traditional dance. This type of research is qualitative research using the action research method (action research). The researcher identified specific problems and determined actions as solutions to these problems. Furthermore, the research refers to the construction method of creating dance in Jacqueline Smith’s book, translated by Ben Suharto, entitled Dance Composition: A Practical Guide for Teachers. The stages of activity include observation, determination of focus and preparation of training materials, transfer of materials, the performance of the Seudati dance, and evaluation of activities. The action is carried out in the form of training in the management of the energy element when dancing the Seudati dance. The material is delivered through audiovisual media and demonstrates it. Based on the process and the research results, it is found that the potential for the sustainability of the creative process can be carried out by the children of Aneuk Metuah studio in every training process in the future. It is hoped that this activity will have a long-term impact on the trainees in managing the elements of movement energy when dancing and increasing the artistic creativity in the studio.Keywords: dance; training; elements of motion; Seudati